Sex-Dependent Metabolic Alterations of Rat Liver After 12-Week Exposition to Haloperidol or Clozapine - von Wilmsdorff, M.; Bouvier, M.-L.; Henning, U.; Schmitt, A.; Schneider-Axmann, T.; Gaebel, W. (Hormone and Metabolic Research, 2014)
Antipsychotic drugs are known to have sex-dependent effects on metabolic homeostasis. Liver plays a crucial role in drug degradation as well as in glucose and lipid metabolism. The present study examines the influence of clozapine and haloperidol on metabolic liver parameters. Over 12 weeks, male and female Sprague-Dawley rats were fed ground pellets containing clozapine or haloperidol. Liver mass was weighed and liver index calculated. Liver transaminases (ALAT, ALP), malondialdehyde, glucose, triglycerides, total cholesterol, HDL-cholesterol, and glycogen were determined. Finally, SREBP-1 and SREBP-2 as well as neutral fat deposits were examined. In male rats fed with clozapine, we found increased liver mass correlated with an increased liver index, high triglyceride levels, a high ratio of SREBP-1, and an elevated neutral fat distribution. Male and female haloperidol treated rats showed decreased liver mass and increased neutral fat deposition. Malondialdehyde was increased in all rats receiving antipsychotic medication indicating elevated oxidative stress. In both male and female clozapine treated rats, we found glycogen depletion related to decreased glucose levels in females. While liver transaminases were unchanged in the clozapine group, ALAT was elevated after haloperidol treatment in both sexes. Chronic clozapine intake exerts sex-dependent effects on hepatic metabolism. Although haloperidol has been shown to change fewer metabolic parameters, it causes oxidative stress and neutral fat deposits in liver tissue in both sexes.
Keywords: glucose; glycogen; lipid metabolism; oxidative stress